(untitled) (TERRA LATINOAMERICANA, 2025)
The Hueyateno micro-watershed is located in the upper part of the Sierra Norte de Puebla and covers 8347 ha. Between 1993 and 2023, it experienced significant land use and cover transformations, reflecting the ef fects of urban and agricultural expansion to the detriment of natural ecosystems. These changes caused forest cover loss, af fecting water regulation and soil stability, which represents a challenge for environmental sustainability. The aim of this study was to analyze spatial and temporal changes to identify transformation patterns and their implications. Landsat satellite images from 1993, 2014, and 2023 were used, processed through supervised classification in geographic information system sof tware, calculating change rates and transition matrices. Results show a forest loss of 2590.80 ha between 1993 and 2023, mainly converted into agricultural areas (1914.43 ha) and urban zones (656.10 ha). Urban growth was initially concentrated in the northern area, progressively extending to the central and southern zones, favored by flatter topographic conditions. Change rates revealed sustained urban expansion, while agricultural land experienced intense growth over 30 years. Territorial planning limitations contributed to landscape fragmentation and the loss of ecosystem services. Therefore, the findings highlight the need for comprehensive land management policies that balance socioeconomic development with environmental conservation. Moreover, integrating spatial and temporal analysis of land use change provides relevant information for designing sustainable strategies in similar micro-watersheds, underlining the importance of this study for informed decision-making.